A flat trend of star formation rate with X-ray luminosity of galaxies hosting AGN in the SCUBA-2 Cosmology Legacy Survey. Issue 3 (17th April 2019) - Ramasawmy, Joanna; Stevens, Jason; Martin, Garreth; Geach, James E
ABSTRACT: Feedback processes from active galactic nuclei (AGN) are thought to play a crucial role in regulating star formation in massive galaxies. Previous studies using Herschel have resulted in conflicting conclusions as to whether star formation is quenched, enhanced, or not affected by AGN feedback. We use new deep 850 $μ$ m observations from the SCUBA-2 Cosmology Legacy Survey (S2CLS) to investigate star formation in a sample of X-ray selected AGN, probing galaxies up to $L_{0.5{\!-\!}7~\rm keV} = 10^{46}$ erg s −1 . Here, we present the results of our analysis on a sample of 1957 galaxies at 1 < z < 3, using both S2CLS and ancilliary data at seven additional wavelengths (24–500 $μ$ m) from Herschel and Spitzer . We perform a stacking analysis, binning our sample by redshift and X-ray luminosity. By fitting analytical spectral energy distributions (SEDs) to decompose contributions from cold and warm dust, we estimate star formation rates (SFRs) for each 'average' source. We find that the average AGN in our sample resides in a star-forming host galaxy, with SFRs ranging from 80 to 600 M⊙ yr −1 . Within each redshift bin, we see no trend of SFR with X-ray luminosity, instead finding a flat distribution of SFR across ∼3 orders of magnitude of AGN luminosity. By studying instantaneous X-ray luminosities and SFRs, we find no evidence that AGN activity affects star formation in host galaxies.